Збірник статей здобувачів вищої освіти другого (магістерського) рівня Навчально-наукового інституту економіки, оподаткування та митної справи Університету ДФС України : у 4 ч. Ч. 3. - ННІ економіки, оподаткування та митної справи; NNI economics, taxation and customs affairs (Ірпінь, 2019)
У збірнику опубліковано статті здобувачів вищої освіти другого (магістерського) рівня. Видання призначене для молодих вчених, аспірантів, здобувачів вищої освіти. The collection publishes articles by students of the second (master's) level of higher education. The publication is intended for young scientists, post-graduate students, students of higher education.
A collection of articles by students of higher education of the second (master's) level of the Educational and Scientific Institute of Economics, Taxation and Customs Affairs of the University of the SFS of Ukraine: at 4 p.m. Part 3.
Keywords: економіка, оподаткування, митна справа; economy, taxation, customs affairs